2015
DOI: 10.1080/10408398.2013.790779
|View full text |Cite
|
Sign up to set email alerts
|

Carotene Degradation and Isomerization during Thermal Processing: A Review on the Kinetic Aspects

Abstract: Kinetic models are important tools for process design and optimization to balance desired and undesired reactions taking place in complex food systems during food processing and preservation. This review covers the state of the art on kinetic models available to describe heat-induced conversion of carotenoids, in particular lycopene and β-carotene. First, relevant properties of these carotenoids are discussed. Second, some general aspects of kinetic modeling are introduced, including both empirical single-resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
49
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 65 publications
7
49
0
1
Order By: Relevance
“…This correlates well with previous studies on the kinetics of β‐carotene isomerization. The isomerization reactions follow first‐order kinetics and as such are independent of concentrations . Studies have also shown the isomerizations to occur fast at high temperatures (>100 °C) leading to mixtures of cis ‐isomers as also seen in the present study …”
Section: Discussionsupporting
confidence: 84%
“…This correlates well with previous studies on the kinetics of β‐carotene isomerization. The isomerization reactions follow first‐order kinetics and as such are independent of concentrations . Studies have also shown the isomerizations to occur fast at high temperatures (>100 °C) leading to mixtures of cis ‐isomers as also seen in the present study …”
Section: Discussionsupporting
confidence: 84%
“…For most vegetables, drying resulted in 10-20% loss of carotenoids , with the increased surface area of dried or powdered products leading to further losses (through autoxidation) unless they were protected from high temperature, air and light. In addition to this, thermal processing may cause significant quantitative changes in carotenoid isomers, due to possible trans to cis isomerization of β-carotene and lutein (Colle, et al, 2015). So, higher retention of cis-isomers was generally recorded in thermal processed fruits and vegetables compared to trans-isomers.…”
Section: Accepted Manuscriptmentioning
confidence: 95%
“…However, high temperatures can lead to isomerization processes, decreasing the food nutritional values. β-carotene and lutein degradation for the formation of cis-isomer (4-40%) during the thermal processing was described in some studies with brassica vegetables (e.g., broccoli and kale) [58]. Thus, a higher retention of cis-isomers was registered in brassica vegetables thermally processed in comparison to trans-isomers, leading to losses in the vitamin A content in these foods.…”
Section: Carotenoidsmentioning
confidence: 98%